Supporting Senior High School Students' Creative Thinking and Collaboration Skills through Combined PBL Model-TAI - Fiqhunnisa, Anindita; Oetomo, Dwi; Fatmawati, Umi (Universitas Pendidikan Indonesia, 2024)
This study aimed to determine whether there is a simultaneous difference in students' creative thinking and collaboration skills when using the Problem-Based Learning (PBL) model integrated with Team Assisted Individualization (TAI). The research employed a quasi-experimental design with a posttest-only control group design. The study population comprised tenth-grade students at SMA N 7 Surakarta during the 2023/2024 academic year. The sample included control and experimental classes selected through cluster random sampling. Data were collected using a creative thinking skills posttest, collaboration observation sheets, and documentation. The hypothesis was tested using MANOVA. The data analysis revealed that the creative thinking and collaboration skills of students in the experimental class were higher than those in the control class. The hypothesis test results indicated that the significance value was 0.021 (sig = 0.021 0.05), leading to the rejection of H0. This finding signifies that there is a simultaneous difference in creative thinking and collaboration skills when applying the PBL model integrated with TAI. It is concluded that the PBL model integrated with TAI creates a significant difference compared to the PBL model alone in fostering students' creative thinking and collaboration skills.